High-dose and low-dose varenicline for smoking cessation in adolescents: a randomised, placebo-controlled trial. (November 2020) - Gray, Kevin M; Rubinstein, Mark L; Prochaska, Judith J; DuBrava, Sarah J; Holstein, Ann R; Samuels, Larry; McRae, Thomas D
Summary: Background: Although cigarette smoking typically begins in adolescence, evidence for successful pharmacological smoking cessation interventions for this population is scarce. In adult smokers, varenicline is the most effective single pharmacotherapy. The aim of this study was to assess the efficacy and tolerability of varenicline for smoking cessation in adolescents. Methods: We did a randomised, placebo-controlled trial with adolescent smokers aged 12–19 years who were seeking treatment to quit at 57 outpatient centres (in the USA, Russia, South Korea, Taiwan, Canada, and Georgia). Participants were randomly assigned (1:1:1) to receive 12 weeks of high-dose varenicline (1 mg twice daily; 0·5 mg twice daily if bodyweight ≤55 kg), low-dose varenicline (0·5 mg twice daily; 0·5 mg once daily if bodyweight ≤55 kg), or placebo, then followed up for 40 additional weeks. At all visits, participants received brief, developmentally tailored smoking cessation counselling (<10 min per session) delivered by a trained counsellor. The primary efficacy outcome was continuous abstinence from weeks 9 to 12, measured via a Nicotine Use Inventory and confirmed by urine cotinine testing. The primary tolerability outcome was frequency of treatment-emergent adverse events, including neuropsychiatric adverse events, occurring after the first dose and within 30 days of the last dose of study medication. This trial is registered with ClinicalTrials.gov, NCT01312909 . Findings: Between April 26, 2011, and Jan 18, 2018, 312 participants were enrolled and completed participation in the study: 109 in the high-dose varenicline group, 103 in the low-dose varenicline group, and 100 in the placebo group. The continuous abstinence rates from week 9 to 12 were 20% (22 of 109) in the high-dose varenicline group, 27% (28 of 103) in the low-dose varenicline group, and 18% (18 of 100) in the placebo group. Abstinence rates between high-dose varenicline and placebo groups (odds ratio [OR] 1·18 [95% CI 0·59–2·37]; p=0·63) and between low-dose varenicline and placebo groups (1·73 [0·88–3·39]; p=0·11) did not differ significantly. Treatment-emergent adverse events occurred in 65 (60%) of 108 participants in the high-dose group, 53 (53%) of 100 in the low-dose group, and 52 (53%) of 99 in the placebo group, and most were rated as mild. Neuropsychiatric treatment-emergent adverse events occurred in 18 (17%) of 108 participants in the high-dose group, 11 (11%) of 100 in the low-dose group, and 12 (12%) of 99 in the placebo group, and none was rated as severe. Interpretation: This trial did not show an advantage in abstinence with varenicline compared with placebo among adolescent smokers. The rates of treatment-emergent adverse events were similar to those in previous trials of adult smokers, raising no new tolerability signals. These findings do not support the use of varenicline as a first-line pharmacotherapy for smoking cessation in adolescents. Funding: Pfizer.